ANALISIS SUPERVISI AKADEMIK KEPALA SEKOLAH DAN MOTIVASI BERPRESTASI TERHADAP KINERJA MENGAJAR (STUDI KASUS DI SMP SUB RAYON 05 KABUPATEN BIREUEN) - Baihaqi, Baihaqi; M., Yusuf (LPPM-UNIKI, 2023)
This research is a survey of junior high school teachers in Rayon 05, Bireuen Regency, which aims to analyze teaching performance factors related to the principal's academic supervision and teacher achievement motivation. Applying quantita-tive research methods with descriptive and associative types between variables. Statistical analysis tools are used as a solution to test hypotheses with path analysis models. The results showed: (1) there was a correlation between exogenous variables (school principal's academic supervision and teacher achievement motivation) of 0.309. 2) there is a direct and indirect effect of the principal's academic supervision on teacher teaching performance, with a change rate of 0.390 or a contribution of 16.61%. (3) there are direct and indirect effects of teacher achievement motivation on teacher teaching performance with a change rate of 0.548, so that the determination is 29.78%. (4) the principal's academic supervision variable together with the teacher's achievement motivation makes a significant contribution to teaching performance of 63.70%. While the rest is due to the role of variables that are not examined at 36.3%. These factors include school culture, teacher competence, school facilities, and others